Mungbean in Southeast Asia and East Africa: Varieties, Practices and Constraints. - Sequeros, Teresa; Ochieng, Justus; Binagwa, Papias H.; Juma, Maurice Ogada; Kangile, Joseph Rajabu; Karimi, Rael; Mbeyagala, Emmanuel K.; Mvungi, Henry; Sanya, Losira Nasirumbi; Nguyen, Thi Tan Loc; Simfukwe, Esther; Suebpongsang, Pornsiri (Agriculture & Food Security, 2021)
Improving the productivity of grain legumes is important to address global challenges of food security and soil degradation. This study’s objective was to quantify the adoption of improved mungbean (Vigna radiata L.) varieties and agricultural practices and to identify production constraints for six countries in Southeast Asia and three countries in East Africa. A Delphi method using expert elicitation was applied at subnational levels and then aggregated to national levels. Each panel employed repetitive and independent questioning of experts. The study organized 31 expert panels involving 387 experts across 9 countries. The share of improved varieties in the planted area, as estimated by the expert panels, was 92% for the Philippines, 91% for Vietnam, 99% for Thailand, 84% for Cambodia, 60% for Indonesia, 35% for Laos, 91% for Kenya, 30% for Uganda and 25% for Tanzania. The average age of improved varieties was 19 years in Asia and 12 years in East Africa. Of the mungbean area in Southeast Asia, 61% was planted to varieties developed by the World Vegetable Center, but this was only 2% in East Africa. Production constraints generally included insect pests and plant diseases, unstable markets with low price and low market demand, and the lack of quality seed of suitable varieties. There are ample opportunities to improve mungbean productivity through wider use of improved varieties and practices, which is important to meet the contemporary challenges of improving human nutrition and agricultural sustainability.
Keywords: Expert elicitation, Technology adoption, Legume, Improved varieties, Innovation